Respiration rate in the high - Lynch C., Alfredo (1942)
The author briefly summarizes the works of Cervelli and of Monge and Pesce on the variations of pulse rate in high altitudes. He then studies the respiration rate after effort at sea level and at high altitude on acclimated men. He classifies the results as normal, bradipneics and polipneics stating and explaining clearly the characteristics of each group, and establishing their percentages.The author studies also the pulse rate after effort, comparing his findings to those of Monge, and pointing out the relations between pulse rate and respiration rate after effort, at sea level and at high altitudes. He also makes determinations In 10 men, not acclimated to high altitudes, who made the Lima-Morococha-Huancayo trip. He studies the adaptation of the pulse and respiratory rate in rest, as well as after effort. He analyzes all these phenomena in the light of the modern views of Physiology, and concludes as follows: 1 ) The respiratory rate at rest is apparently the same at sea level and in high altitudes. 2) The respiratory rate in andean men, responds to effort in a different way (andean type) to that of the men of the Coast (coast type ). 3) Concerning the post-effort respiratory rate, there is a higher percentage (14 %) of bradipneics among andean men than among the men of the Coast (4 %). 4) The same can be saids of the polipneics which are in a proportion of 12 % among the andean men, against only 1% in the Coast. 5) altitude, (50 %). 6) Comparing the reactions of pulse and respiration at high the percent reactions of "andean type" is higher in pulse than in respiration (26 %). The type of response to effort, changes by ascending.